Concentrated solar power plants: A critical review of regional dynamics and operational parameters. (January 2022) - Goyal, Naman; Aggarwal, Akshansh; Kumar, Anil
Graphical abstract: Highlights: 112 concentrated solar power plants are currently operational globally. Parabolic Trough is the leading CSP technology. Thermal Oil and parabolic trough are the most commonly used HTF/HSM and CSP. Linear relationship is found between plant area and electricity generated per year. South America and Africa holds significant potential for CSP development. Abstract: Paper presents a regionally segregated overview of the globally distributed operational Concentrated Solar Power (CSP) plants. A holistic approach was followed by dividing the global map into 5 different regions (Americas, Africa, Europe, Asia and Australia) by covering 112 currently operational CSP plants. The objective of the research methodology used is to enable concerned regional developers to study the local trend followed in brief and compare the same with the trend followed in other regions. Region 3 (Europe) generates 6338.33 GWh/yr of electricity and accommodates more than 50% of globally operational CSP plants. Parabolic trough/Thermal oil is the most preferred combination of CSP technology/Heat Transfer Fluid (HTF) and is used in 46 plants globally. Region 5 (Australia) produces the lowest annual electricity generation of 3900 MWh/yr but still holds great potential for numerous upcoming plants. Annual electricity generation of plants when plotted with area occupied displayed a linear trend for all the regions. Linear pattern observed also included 2–3 outliers indicating significant under or over performance of specific sites. Regional distribution enables a modular study and analysis, aiding future research and development in solar thermal energy. Accumulated information and data presented serve as a brief guide reducing the gap between social structures and latest technological advancements.